Friday

July 25, 2014

July 25, 2014

Posted by **Margie** on Saturday, October 14, 2006 at 2:12pm.

3x - y = 10

-x + y = -4

(3, -7)

(-1, 3)

(3, -1)

(3, 1)

Follow the example I gave in your previous question. I'm not going to do all of them.

You want to eliminate one of the variable and solve. Then substitute into an equation and sovle for the other variable.

If you add the equations together

3x - y = 10

-x + y = -4

you get

2x = 6

Solve for x and substitute into either equation to solve for the other variable.

**Related Questions**

math - Determine whether the ordered pair is a solution of the inequality (5, 12...

alegebra - Solve the system of equations by graphing. Then classift the system ...

Algebra333333!!! - Choose the ordered pair that is a solution to the system of ...

algebra - Which of the following ordered pairs is included in the solution set ...

math - what does it mean for an ordered pair to be a soltuin of both equations? ...

Math Help PLEASE - Solve the system of equations by graphing then classify the ...

Intermediate Algebra - Solve the following system of equations. x+4y=5 x=6-4y ...

Math - True or false, A solution of a system of linear equations is an ordered ...

Math - Which ordered pair is a solution of the system of equations y=x^2-x-20 ...

Algebra 1a - Solve the following system of equations. x+3y=6 x=8-3y What is the ...